2004
DOI: 10.1155/2005/961613
|View full text |Cite
|
Sign up to set email alerts
|

Probable Linezolid‐Induced Pancytopenia

Abstract: A 75-year-old male outpatient with cardiac disease, diabetes, chronic renal insufficiency and iron deficiency anemia was prescribed linezolid 600 mg twice daily for a methicillin-resistant Staphylococcus aureus diabetic foot osteomyelitis. After one week, his blood counts were consistent with baseline values. The patient failed to return for subsequent blood work. On day 26, he was admitted to hospital with acute renal failure secondary to dehydration, and was found to be pancytopenic (erythrocytes 2.5x10(12)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Kuter and Tillotson reported 11 cases out of 13 where pancytopenia occurred after 21 days on linezolid prescription and improved two weeks after withdrawal [9]. Lakhani et al reported pancytopenia in elderly patients receiving linezolid 600 mg twice a day [12]. In our patient, the first symptom appeared 32 days after the start of linezolid therapy and its discontinuation led to resolution of pancytopenia within 21 days.…”
Section: Discussionmentioning
confidence: 53%
“…Kuter and Tillotson reported 11 cases out of 13 where pancytopenia occurred after 21 days on linezolid prescription and improved two weeks after withdrawal [9]. Lakhani et al reported pancytopenia in elderly patients receiving linezolid 600 mg twice a day [12]. In our patient, the first symptom appeared 32 days after the start of linezolid therapy and its discontinuation led to resolution of pancytopenia within 21 days.…”
Section: Discussionmentioning
confidence: 53%
“…In this case and a number of other cases involved elderly patients (60 years old or older) receiving linezolid 600 mg twice daily. 7,911 Age did not significantly affect linezolid’s pharmacokinetics with single 600 mg oral doses. 21 In addition, our patient had renal dysfunction (creatinine clearance ranged from 40 to 60 mL/min).…”
Section: Discussionmentioning
confidence: 84%
“…6 Case reports of linezolid-induced thrombocytopenia have been previously published. 711 This case of thrombocytopenia is believed to be associated with linezolid therapy in a patient with vancomycin-resistant enterococci (VRE) abdominal infection.…”
Section: Introductionmentioning
confidence: 99%
“…After the use of linezolid was approved in the USA, there were 72 cases of haematological abnormalities reported among 55 000 patients within the first six months, of the 72 cases reported, pancytopenia accounted for 13 of these cases 2. Lakhani et al reported a further case of pancytopenia with linezolid therapy 6. Though rare, the literature certainly recognises pancytopenia as a side effect.…”
Section: Discussionmentioning
confidence: 99%